CONTEMPORARY PERSPECTIVES ON AYURVEDA & CHANGING PARADIGMS (AYUSHDHARA, 2015)
Medical science is advancing by leaps and bounds, exploring the intricacies and unravelling the mysteries of human life. Ever since the dawn of his turbulent history, man has evolved several ways of coping with illness. Every country has developed a medical system presenting a unique configuration designed to be compatible with its future, meeting the needs of its population. Thus the ‘traditional medicine’, which is full of experiences, astute observations and fancy formulae reflecting a combination of inspiration, intuition, information, facts and results, has incarnated.Ayurveda, literally meaning “the science of lifespan”, is the traditional medicine system of India. Its natural healing modality has been in existence for about 5000 years. Ayurveda is widely acknowledged to be the world’s oldest system of healthcare. WHO regards it as “the world’s most ancient, scientific, holistic, complete, natural system of healthcare and is the forerunner of all other great systems practiced today.”